Contributions to twentieth century total column ozone change from halocarbons, tropospheric ozone precursors, and climate change. Issue 23 (3rd December 2013) - Reader, M. C.; Plummer, D. A.; Scinocca, J. F.; Shepherd, T. G.
<x xml:space="preserve">Abstract</x> [1] We investigate ozone changes from preindustrial times to the present using a chemistry‐climate model. The influence of changes in physical climate, ozone‐depleting substances, N2O, and tropospheric ozone precursors is estimated using equilibrium simulations with these different factors set at either preindustrial or present‐day values. When these effects are combined, the entire decrease in total column ozone from preindustrial to present day is very small (−1.8 DU) in the global annual average, though with significant decreases in total column ozone over large parts of the Southern Hemisphere during austral spring and widespread increases in column ozone over the Northern Hemisphere during boreal summer. A significant contribution to the total ozone column change is the increase in lower stratospheric ozone associated with the increase in ozone precursors (5.9 DU). Also noteworthy is the near cancelation of the global average climate change effect on ozone (3.5 DU) by the increase in N2O (−3.9 DU).